Logística de la comercializadora Mega Proprinec - Barragán Dávila, Yasyla Marilyn (2020)
In the "Mega proprinec trading company" its logistics are inadequate because the commercial space is divided into two sections; reason for which it cannot offer a wide and comfortable place for the attention of its clients, with the objective of determining the factors that influence the inadequate logistics of the “Mega proprinec trading company”, in which it is related to the research sub-line administrative management model because it is a search for information that involves administrative processes. The methodology established in the present case study is the descriptive method, which admitted analyzing the difficulties that are promoted in the “Mega proprinec trading company”, the analytical method was also used as it narrates the experiences achieved during the course of the research, determining characteristics of the elements that intervene in the problem.